2019
DOI: 10.1542/peds.2019-3224
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Bariatric Surgery for Pediatric Patients With Severe Obesity

Abstract: Severe obesity affects the health and well-being of millions of children and adolescents in the United States and is widely considered to be an "epidemic within an epidemic" that poses a major public health crisis. Currently, few effective treatments for severe obesity exist. Metabolic and bariatric surgery are existing but underuse treatment options for pediatric patients with severe obesity. Roux-en-Y gastric bypass and vertical sleeve gastrectomy are the most commonly performed metabolic and bariatric proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(64 citation statements)
references
References 62 publications
0
59
0
5
Order By: Relevance
“…A recent policy statement from the American Academy of Pediatrics (AAP) recommended improved access for pediatric patients "to multidisciplinary programs that provide high quality pediatric metabolic and bariatric surgery" with no lower age limit given emerging long-term outcome data (15,16,48). With this shift in policy comes an even greater role for pharmacotherapy treatment as prior studies have found that AOMs serve as a useful adjunct in postsurgical patients following bariatric surgery to treat inadequate WL or weight regain (49)(50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent policy statement from the American Academy of Pediatrics (AAP) recommended improved access for pediatric patients "to multidisciplinary programs that provide high quality pediatric metabolic and bariatric surgery" with no lower age limit given emerging long-term outcome data (15,16,48). With this shift in policy comes an even greater role for pharmacotherapy treatment as prior studies have found that AOMs serve as a useful adjunct in postsurgical patients following bariatric surgery to treat inadequate WL or weight regain (49)(50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…According to the most recently available data from the NHANES, the prevalence of severe obesity from 2015 to 2016 was 1.9% among children and adolescents 2 to 19 years old, with 4.5% of adolescents age 16-19 years old affected by severe obesity (1). While strides have been made toward encouraging the utilization of metabolic and bariatric surgery (MBS) for pediatric patients with severe obesity, with definitive guidance from organizations such as the American Academy of Pediatrics (AAP) and the American Society of Metabolic and Bariatric Surgery (ASMBS) (14)(15)(16)(17), there remains a gap in care for patients who have been refractory to lifestyle modifications but do not meet criteria for MBS.…”
Section: Introductionmentioning
confidence: 99%
“…Surgery. Metabolic and bariatric surgery in the pediatric population provides evidence-based effective treatment of severe obesity and related comorbid diseases in the USA [87].…”
Section: Healthy Food Subsidization and Taxation Of Junk Foodmentioning
confidence: 99%
“…There are many barriers regarding consideration of MBS among children and adolescents with severe obesity. While access to care is multifactorial, race and socioeconomic status is are important considerations in regard to insurance authorization for surgery [114]. Just under 50% of pediatric patients who qualify for surgery receive insurance coverage initially following request for authorization [114,115].…”
Section: Metabolic and Bariatric Surgerymentioning
confidence: 99%
“…While access to care is multifactorial, race and socioeconomic status is are important considerations in regard to insurance authorization for surgery [114]. Just under 50% of pediatric patients who qualify for surgery receive insurance coverage initially following request for authorization [114,115]. While age less than 18 years old is the most common reason for denial, Perez and colleagues have shown authorization for bariatric surgery is most common among White females with private insurance [115].…”
Section: Metabolic and Bariatric Surgerymentioning
confidence: 99%